'I Know What Freedom and Responsibility Mean Now': Narratives of Autonomous Adulthood among Korean Students in the USA. (September 2018) - Jung, Gowoon
This article analyses narratives of autonomous adulthood among Korean international students at an American state university. I categorize student narratives in terms of the number of activities associated with achieving adulthood markers and the efficacy of individual agency. A broad perspective considers a wide variety of activities to contribute to autonomous adulthood and valourizes individual agency. A narrow perspective focuses on activities tailored to one's career, and downplays individual agency compared to larger institutional-structural factors. I examine these narratives among three groups of international students, depending on their time of arrival: pre-college migrants who moved to the USA during middle or high school, college-migrants who arrived during the first or second year of undergraduate college and post-college migrants who came for advanced degrees (e.g., MA, PhD). The finding suggests that students negotiate agency and structure differently depending on their past and current experiences in the sending and receiving countries.